2010
DOI: 10.1002/per.753
|View full text |Cite
|
Sign up to set email alerts
|

Predicting academic success with the Big 5 rated from different points of view: Self‐rated, other rated and faked

Abstract: Self‐ratings of personality predict academic success above general intelligence. The present study replicated these findings and investigated the increment of other‐ratings or intentionally distorted self‐ratings. Participants (N = 145) had to compile a personality questionnaire twice. First they were given neutral instructions. The second time they were asked to imagine a specific applicant setting. Furthermore, two peers rated each participant. Additionally, verbal, numerical and figural reasoning scores wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 27 publications
3
40
0
1
Order By: Relevance
“…However, other studies reported no or even positive effects [43][44][45][46]. For Extraversion, a positive correlation with performance was reported in elementary school but became negative when kids grew older [47][48][49]. This might be due to the two components of Extraversion: Ambition (referring to the need for dominance) and Sociability (referring to the need for affiliation).…”
Section: Personality and Scholastic Performancementioning
confidence: 97%
See 2 more Smart Citations
“…However, other studies reported no or even positive effects [43][44][45][46]. For Extraversion, a positive correlation with performance was reported in elementary school but became negative when kids grew older [47][48][49]. This might be due to the two components of Extraversion: Ambition (referring to the need for dominance) and Sociability (referring to the need for affiliation).…”
Section: Personality and Scholastic Performancementioning
confidence: 97%
“…Another explanation could be that within the field of intelligence research, very elaborate models have been developed, including different intelligence facets: verbal, numerical, and figural reasoning abilities [87]. According to Brunswik's lens model [88], symmetry between predictor and criterion could increase correlations (see also [49,89]). Future studies should therefore strive to apply broad measures of Gf in Chinese contexts.…”
Section: Fluid Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows that in the faking conditions, the reliabilities of the facets generally became lower, and in some cases were rather low (e.g., .19 for activity in the lawyer condition). Facet reliabilities have generally been shown to decrease under faking conditions (McCann, 2013;Ziegler, Danay, Schölmerich, & Bühner, 2010). We elaborate on this in the Limitations and Future Studies section.…”
Section: Descriptive Statisticsmentioning
confidence: 94%
“…Einzelne Facetten der Big Five beeinflussen den Studienerfolg (Trapmann, Hell, Hirn & Schuler, 2007;) und Berufserfolg (Judge, Higgins, Thoresen & Barrick, 1999). Sie liefern dazu in beiden Fällen einen inkrementellen Beitrag über die Intelligenz hinaus (Judge et al, 1999;Ziegler, Danay, Schölmerich & Bühner, 2010). Persönlich-keitsmerkmale können damit ein Mehrgewinn für Zulassungsverfahren sein, auch wenn durch deren Verwendung Faking eine zu adressierende Problematik wird .…”
Section: Theoretischer Hintergrundunclassified